What to do About (Housing) Injustice? Developing the Social Connection Model’s Prioritization and Action Guidance and Investigating Landlords’ Responsibility for Housing Injustice - Batista, Mackenzie (My University, 2023)
This thesis develops the prioritization guidance and action guidance provided by Iris Marion Young’s Social Connection Model of responsibility for injustice. Young’s parameters of reasoning are limited in their ability to assist responsible agents in determining what they ought to do to fulfill their responsibilities, as they are severed from the structural analysis characteristic of the rest of the SCM. This thesis addresses the resulting limitations by developing categories of prioritization and an action guidance framework. I develop 6 categories of prioritization: power, benefit, interest, centrality, contribution, and control. Applied to social-group-based analysis, these categories determine the strength of the prioritization claim which a given injustice holds over a given social group. The action guidance framework takes the perspective of the political community and works its way through three questions and their corresponding considerations: “What can we do?” –structural change, altering practices, and harm alleviation; “How can we do it?” –understanding sub-issues and sub-options, determining interests, and organizing collectives; and “What can I do?” –eliminating contributory behaviours, and considering personal circumstances. Through this framework, agents can analyze the capacities of the political community and the structures of an injustice to determine which projects should be undertaken and how agents ought to contribute. Finally, the developments of this thesis are applied to the case of landlords and housing, therein establishing the necessity of landlords abandoning rental profits so as to fulfill and not contradict their responsibility to eliminate housing injustice.
Keywords: Injustice; Landlords; Housing; Prioritization; Action Guidance; Definancialization; Profit; Rent; Responsibility; Collective Responsibility; Iris Marion Young; Social Connection Model; Political Responsibility; Shared Responsibility; Landlord; Social Groups